Development of Warm In-Place Recycling Technique as an Eco-Friendly Asphalt Rehabilitation Method - Byungkyu Moon; Ashkan Bozorgzad; Hosin (David) Lee; Soo-Ahn Kwon; Kyu-Dong Jeong; Nam-Joon Cho (Infrastructures, 2021)
Cold In-place Recycling (CIR) has been widely used in the world since it is easy to apply it in the field at a low cost. However, it is not normally used as a surface layer as a result of its inconsistent quality due to an excessive amount of fine aggregates pulverized during the milling process. Hot In-place Recycling (HIR) can retain the original shape of the aggregates, but it often produces a large amount of Volatile Organic Compounds (VOCs). Therefore, a third in-place recycling technique is introduced in this paper: Warm In-place Recycling (WIR). The WIR technique overcomes the limitations of both CIR and HIR techniques by lowering a heating temperature while adding a Tetraethylenepentamine (TEPA)/Soybean/SBS additive. To identify the effect of the additive on the RTFO-aged binder, viscosity and dynamic modulus values were measured at different temperatures. Based on Hamburg Wheel Tracking (HWT) and Disc-Shaped Compact Tension (DCT) tests, the additive improved the moisture susceptibility and low temperature cracking resistance. The indirect infrared heating equipment reduced the emission by lowering the pavement surface heating temperature by 20 °C from 140 to 120 °C. Compared with the heating at 140 °C, the LPG usage for heating at 140 °C was lowered by 21%. The proposed WIR equipment with an additive would revolutionize the in-place recycling practices.